2010
DOI: 10.1159/000319618
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Aortic Balloon Pump Improves Clinical Prognosis and Attenuates C-Reactive Protein Level in Acute STEMI Complicated by Cardiogenic Shock

Abstract: Objectives: Intra-aortic balloon pump (IABP) plays a pivotal role in the treatment of cardiogenic shock (CS) complicating acute ST-segment elevation myocardial infarction (STEMI). However, the influence of IABP on the inflammatory response has not been well evaluated. We sought to assess the effects of IABP support upon C-reactive protein (CRP) levels in patients with STEMI complicated by CS undergoing percutaneous coronary intervention (PCI). Methods: This was a prospective study and a total of 91 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 42 publications
0
6
1
Order By: Relevance
“…Through sensitivity analysis, upon elimination of articles with a low-quality score, all results of the heterogeneity test showed low heterogeneity. Paired researchers reassessed the three articles with low-quality scores [ 21 , 23 , 56 ]. We believe that the reasons for the high heterogeneity may be related to the different aetiologies of CS and the different designs of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Through sensitivity analysis, upon elimination of articles with a low-quality score, all results of the heterogeneity test showed low heterogeneity. Paired researchers reassessed the three articles with low-quality scores [ 21 , 23 , 56 ]. We believe that the reasons for the high heterogeneity may be related to the different aetiologies of CS and the different designs of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Another safety concern around DS is theoretical time related risk of coronary reocclusion and its consequences.Even social issues of a patient having negative outcomes despite a procedure being done are difficult to tackle practically especially in young patients. It is wise to have allow threshold for use of IABP in DS as it helps to maintain optimal perfusion to infracted area and also gives therapeutic safety edge in case emergency intervention needed [27].In conclusion, DS strategy is double edged sword with the possibly lesser risk of no reflow, however at the expense of risk of re-occlusion, which could be life threatening in certain scenarios.…”
Section: Deferred Stenting Strategymentioning
confidence: 99%
“…Hence, better solution theoretically for this problem is meshed stents (MGUARD), which trap the thrombotic muck, though 1 ST generation of these stents didn't show any benefit over routine DES, however results with 2 nd generation meshed stents are awaited and they hold a promise for future [44]. DS is therefore selectively advocated in subset of patients who are at increased risk of MVO such as increased age (i.e., 65 years of age or older), duration of symptoms > 6 h; heavy thrombus burden (TIMI grade 2 or higher), long lesion length (>24 mm), small vessel diameter (i.e., <2.5 mm), and clinical signs of acute microvascular injury after initial reperfusion with persistent ST-segment elevation >50% [25][26][27][28][29]. Is preferred over DS when the patient has cardiogenic shock, STEMI with Killip class III-IV or presenting as ventricular fibrillation, or sustained ventricular tachycardia and RVMI because the prognosis is very bad with these cases.…”
Section: Head To Head Trailsmentioning
confidence: 99%
“…However, only 40 cases were analyzed and the interval from symptom onset to PCI was on average 11 h, with a trend to longer time intervals in the IABP group [7] . The interval from symptom onset to PCI in the study by Gu et al [4] was much shorter ( ! 5 h), but their results need to be confirmed in a randomized clinical trial.…”
mentioning
confidence: 89%
“…The physiologic and hemodynamic benefits of IABP are well established and include a decrease in systolic blood pressure and an increase in diastolic blood pressure with resultant unloading of the left ventricle and increased coronary blood flow, respectively [2,3] . In a recent issue of Cardiology , Gu et al [4] proposed an additional benefit of IABP in attenuating the inflammatory response to cardiogenic shock assessed by C-reactive protein (CRP) levels [5] .…”
Section: Intra-aortic Balloon Counterpulsation (Iabp) Is An American mentioning
confidence: 99%